Politics of Psychoanalytic Knowledge: Canguilhem’s Reading of Freud - Annagiulia Canesso (University of Bologna, 2021)
Georges Canguilhem has never systematically discussed Sigmund Freud’s thinking. This essay aims to reconstruct Canguilhem’s reading of Freudian psychoanalysis, highlighting its strategic use within the framework of Canguilhem’s controversy against psychology. From this point of view, knowledge is established as a field of political struggle: unlike psychology and its deterministic and normalizing drifts, psychoanalysis allows Canguilhem to affirm the irreducibility of thought to brain localizations, to emphasize its erratic power and to think the constitution of an eccentric subjectivity.